2020
DOI: 10.1016/j.ijid.2020.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of early acute kidney injury in infective endocarditis: A retrospective cohort study

Abstract: The incidence of acute kidney injury (AKI) in infective endocarditis (IE), its risk factors and consequences on patient and renal survival remain debated. Methods: Patients hospitalized for a first episode of IE (possible or definite according to modified Duke criteria) between 2013 and 2016 were included. The primary endpoint was to determine risk factors for early AKI (E-AKI) during the first week of management of IE. Results: A total of 276 patients were included: 220 (79.7%) had definite IE and 56 (20.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Second, infection and heart failure in IE are accompanied by the excessive activation of the body's immune system, a loss of appetite and dietary restrictions in patients, which often lead to the consumption of nutrients and the further reduction of albumin (19). Finally, acute renal failure occurs in about 6-30% of IE patients and is a common complication in this population, which results in the loss of albumin from urine (2,14). These causes are also risk factors of in-hospital death and postoperative adverse cardiovascular events in IE patients (12)(13)(14)(15)20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, infection and heart failure in IE are accompanied by the excessive activation of the body's immune system, a loss of appetite and dietary restrictions in patients, which often lead to the consumption of nutrients and the further reduction of albumin (19). Finally, acute renal failure occurs in about 6-30% of IE patients and is a common complication in this population, which results in the loss of albumin from urine (2,14). These causes are also risk factors of in-hospital death and postoperative adverse cardiovascular events in IE patients (12)(13)(14)(15)20).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, acute renal failure occurs in about 6-30% of IE patients and is a common complication in this population, which results in the loss of albumin from urine (2,14). These causes are also risk factors of in-hospital death and postoperative adverse cardiovascular events in IE patients (12)(13)(14)(15)20). Conversely, from the perspective of pathophysiological function, albumin may have a protective effect on inflammation and oxidative stress-related endothelial dysfunction (21), and the normal function of the immune response system depends on metabolism and nutritional status (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, death-censored graft survival after IE also appeared unexpectedly low, with half of the grafts lost after four years, versus 13% in the controls after the same delay. Endocarditis is known to result in acute and long-term kidney complications [ 30 ] due to infectious, post-infectious, immunological, or drug-related mechanisms. Our study was not designed to explore the cause of renal failure in the patients who were included.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we should be careful about Contrast-Induced Nephropathy (CIN) when performing cerebral CTA. A retrospective cohort study showed that the incidence of acute kidney injury (AKI) was 54.3% in infective endocarditis patients [14]. Implementation of a preventive strategy involving good hydration pre-and post-CT together with the use of low osmolality contrast media will reduce the risk of CIN [15].…”
Section: Discussionmentioning
confidence: 99%